Characteristics of Successful Internal Medicine Resident Research Projects: Predictors of Journal Publication Versus Abstract Presentation. (August 2018) - Atreya, Auras R.; Stefan, Mihaela; Friderici, Jennifer L.; Kleppel, Reva; Fitzgerald, Janice; Rothberg, Michael B.
Abstract : Purpose: To identify the characteristics of successful research projects at an internal medicine residency program with an established research curriculum. Method: The authors collected data about all research projects initiated by or involving medicine residents from 2006 to 2013 at Baystate Medical Center, using departmental files and institutional review board applications. Resident and mentor characteristics were determined using personnel files and Medline searches. Using multivariable models, the authors identified predictors of successful completion of projects using adjusted prevalence ratios (PRs). The primary outcome was manuscript publication, and secondary outcome was publication or regional/national presentation. Finally, residents were surveyed to identify barriers and/or factors contributing to project completion. Results: Ninety-four research projects were identified: 52 (55.3%) projects achieved the primary outcome and 72 (76.5%) met the secondary outcome, with overlap between categories. Most study designs were cross-sectional (41; 43.6%) or retrospective cohort (30; 31.9%). After adjustment, utilization of the epidemiology/biostatistical core (PR = 2.09; 95% CI: 1.36, 3.21), established publication record of resident (PR = 1.54; 95% CI: 1.14, 2.07), and resident with U.S. medical education (PR = 1.39; 95% CI: 1.02, 1.90) were associated with successful project completion. Mentor publication record (PR = 3.13) did not retain significance because of small sample size. Most respondents (65%) cited "lack of time" as a major project barrier. Conclusions: Programs seeking to increase resident publications should consider an institutional epidemiology/biostatistical core, made available to all residency research projects, and residents should choose experienced mentors with a track record of publications. Abstract : Supplemental Digital Content is available in the text.